Analysis of The Influence of Brand Trust and Brand Image on Customer Loyalty of Toyota Family Car Product - Noer Soetjipto; Luh Komang Candra Dewi; Ratnawita; Dian Ariani; Harimurti Wulandjani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study attempts to examine how customer loyalty is affected by brand trust and image for one of Toyota's best-selling vehicles in Indonesia. The study's sample consists of one city residents in Indonesia who drive vehicles. Data collection for this study has been done using a convenience sample strategy. In this study, there are 100 participants, all of them live in the city and drive vehicles. According to the study's findings, brand loyalty for Toyota cars is significantly influenced by both brand image and brand trust at the same time. Partially, brand trust and image have a big impact on how loyal Toyota automobile buyers are.